Hydraulic and electrical regulations of pumps as turbines for energy recovery in water distribution networks: Energy and economic analysis - Lucrezia Manservigi; Valentina Marsili; Filippo Mazzoni; Giulia Anna Maria Castorino; Saverio Farsoni; Enzo Losi; Stefano Alvisi; Marcello Bonfè; Marco Franchini; Pier Ruggero Spina; Mauro Venturini (Cambridge Prisms: Water)
In water distribution networks (WDNs), pressure limitation represents an effective strategy to reduce water losses. This goal can be achieved by means of pressure reducing valves (PRVs), which dissipate exceeding hydraulic energy. For more sustainable management of water systems within a circular economy framework, PRVs can be replaced with energy-producing devices, such as pumps as turbines (PATs). This study presents a general approach for the selection of the optimal PAT to install in a given WDN. The approach assesses the techno-economic feasibility of a fleet of turbomachines by evaluating the rate of energy recovery, the levelized cost of electricity and the payback period of each PAT. Two PAT regulation strategies are accounted for, namely hydraulic and electrical regulations. The approach is applied to a real-world case study consisting of a WDN in Northern Italy that supplies approximately 5,000 users. In addition, a fleet of 16 turbomachines is considered, of which the experimental characteristic curves are available in both pump and turbine modes. The analyses carried out in this article allow selecting the optimal PAT to install within the considered WDN, which recovers 44.1 % of the hydraulic energy of the network with a maximum investment cost of € 24,500.